2018
DOI: 10.11591/ijphs.v7i1.8398
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity Pattern among Out-Patients Attending Urban Health Training Centre in Srinagar

Abstract: <p>The current study was designed to identify the morbidity pattern of out-patients attending Urban Health Training Centre in an urban area of a medical college in Srinagar, Pauri Garhwal district, Uttarakhand, North India. The present study record-based retrospective study was conducted among the out-patients attending the regular clinic at the Urban Health Training Centre, of a medical college in Srinagar city of Uttarakhand State of North India during the study period of one year in 2014. Data was ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 1 publication
0
3
1
Order By: Relevance
“…A study of morbidity patterns of outpatients reported for a city in India, showed that endocrine, nutritional and metabolic diseases accounted for 8.1% of the total patients visiting an urban healthcare training centre. Moreover, patients with circulatory diseases accounted for 27.5% [ 21 ], which was higher than that reported in this study. Possible differences could be that patients in our study were relatively younger, and only included men.…”
Section: Discussioncontrasting
confidence: 65%
See 2 more Smart Citations
“…A study of morbidity patterns of outpatients reported for a city in India, showed that endocrine, nutritional and metabolic diseases accounted for 8.1% of the total patients visiting an urban healthcare training centre. Moreover, patients with circulatory diseases accounted for 27.5% [ 21 ], which was higher than that reported in this study. Possible differences could be that patients in our study were relatively younger, and only included men.…”
Section: Discussioncontrasting
confidence: 65%
“…The costs of NCD treatments place a considerable burden on household income. Studies from India showed that high out-of-pocket expenditure for healthcare related to NCDs is significant in contributing to poverty [ 21 , 22 ]. An estimated 1.4 to 2 million Indians experienced catastrophic spending in 2004, and 600,000 to 800,000 people were impoverished by the costs of caring for cardiovascular disease and cancer [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with the so-called male-female health-survival contradiction survival paradox that women have poor health but less serious comorbidities, leading to longer life expectancy. [13] In joint replacement, the overall number of frail people gradually increased. The results of this study suggested that the demand to improve the quality of life for frail patients has increased in recent years.…”
Section: Total Hip Arthroplasty Cohortmentioning
confidence: 99%